Urgensi Peralihan Kewenangan Sertifikasi Jaminan Produk Halal Majelis Ulama Indonesia Kepada Badan Penyelenggara Jaminan Produk Halal - Ibnu Salam Al-Mawarid; Siti Ngainnur Rohmah (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
For Muslims in Indonesia, halal certification is very important in order to avoid things that are forbidden by religion. Initially this certification was carried out by the MUI, but now this role has been given to the government through the establishment of the Halal Product Guarantee Agency (BPJPH). The purpose of this study is to explain the role of the MUI and the Halal Product Assurance Organizing Agency (BPJPH) in implementing Halal Product Assurance certification in Indonesia. The research method used in this study is the method of literature as normative legal research, with a statutory and historical approach. Primary legal materials, namely Law Number 33 of 2014 concerning Guarantees for Halal Products, Secondary legal materials come from books, legal journals, and the internet. The results of this study state that the role of MUI and BPJPH in implementing Halal Product Guarantee Certification in Indonesia is as partners in order to realize good Halal Product Assurance in Indonesia as stated in article 21 of Government Regulation No. 31 of 2019. The forms of cooperation between MUI and BPJPH include Halal Auditor Certification, Product Halal Determination, and LPH Accreditation.Keywords: Halal Product Act; BPJPH; MUI AbstrakBagi umat muslim di Indonesia, sertifikasi halal menjadi sangat penting agar terhindar dari hal-hal yang diharamkan oleh agama. Pada awalnya sertifikasi ini dijalankan oleh MUI, namun saat ini peranan tersebut sudah diberikan kepada pemerintah melalui pembentukan Badan Penyelenggara Jaminan Produk Halal (BPJPH). Tujuan penelitian ini adalah untuk menjelaskan Peran MUI dan Badan Penyelenggara Jaminan Produk Halal (BPJPH) dalam pelaksanaan sertifikasi Jaminan Produk Halal di Indonesia. Metode penelitian yang digunakan dalam penelitian ini adalah metode kepustakaan sebagai penelitian hukum normatif, dengan pendekatan undang-undang dan pendekatan historis. Bahan hukum Primer yakni Undang-Undang Nomor 33 Tahun 2014 Tentang Jaminan Produk Halal, Bahan Hukum Sekunder berasal dari buku, jurnal hukum, dan internet. Hasil penelitian ini menyatakan bahwa Peran MUI dan BPJPH dalam pelaksanaan Sertifikasi Jaminan Produk Halal di Indonesia adalah sebagai mitra kerja demi mewujudkan Jaminan Produk Halal yang baik di Indoesia sebagaimana yang tercantum pada pasal 21 Peraturan Pemerintah No 31 Tahun 2019. Adapun bentuk kerjasama MUI dan BPJPH meliputi Sertifikasi Auditor Halal, Penetapan Kehalalan Produk, dan Akreditasi LPH.Kata Kunci: Undang-Undang Produk Halal; BPJPH; MUI